Efektivitas Ancaman Pidana Denda Terhadap Pertambangan Tanpa Izin Dalam Amandemen Undang-Undang Minerba - Pudyatmoko, Y. Sri (UI Scholars Hub, 2025)
The aim of this research is to analyze the effectiveness of the threat of criminal fines in amendments to the Law on Minerals and Coal. One of the things that stands out in the amendments to the Law on Mineral and Coal is the change in the threat of criminal sanctions against perpetrators of mining without a permit, from the original threat of a maximum prison sentence of 10 years to 5 years, and a maximum fine of 10 billion rupiah to 100 billion rupiah. This article examines these arrangements. In this paper, doctrinal research and comparison of a number of judicial decisions is carried out. From research it is known that there are many decisions that impose light fines and there are also some decisions that impose very heavy fines but are accompanied by very light substitute imprisonment. From a number of existing decisions it can be seen that setting the threat of such high criminal fines in law does not guarantee effectiveness in law enforcement. Under these conditions, the objectives of punishment cannot be achieved properly. There are a number of alternatives to solve this problem.